Wizard of watts [electronics engineering education]. - Perry, T.S (IEEE spectrum)
IEEE Medal of Honor winner, James D Meindl, blazed an adventure-packed trail in low-power semiconductors and took generations of graduates students along with him. Meindl, a professor of microelectronics at the Georgia Institute of Technology, says that the most important part of his job is making graduate school fun and exciting. This paper presents a story of Meindl that made an impact on his students' careers and on the field he loves